ANALYSIS OF EDUCATORS AND EDUCATION STAFF MANAGEMENT IN PRIMARY SCHOOL QUALITY IMPROVEMENT - Sunaengsih, Cucun; Jatnika, Jamil; Alifia, Silvy Lafthi; Latifah, Latifah; Solihah, Endang (Universitas Pendidikan Indonesia, 2019)
Educators and education staff are primary aspects of education that contribute to school quality improvement. High-quality educators and education staff will lead to high-quality school. However, not all educators and education staff have good quality, due to low-quality management. With this in mind, this study aims to discover the implementation of educators and education staff management in a primary school in West Java, Indonesia. It is found that (1) the ideal ratio of educators and staff has not been achieved, (2) temporary educators are far from being prosperous, in terms of monetary compensation, and (3) training programs for educators and education staff are very limited. These finding indicate that the planning and development process for educators and education staff require an in-depth analysis.